Oxyresveratrol Modulates Genes Associated with Apoptosis, Cell Cycle Control and DNA Repair in MCF-7 Cells - Radapong, Sarayut; Chan, Kelvin; Sarker, Satyajit D.; Ritchie, Kenneth J. (Frontiers in Pharmacology, 2021)
Oxyresveratrol (OXY) is a small molecule of phytochemical known as hydroxystilbenoids, which have been reported significantly important biological activities. The aim of this study was to elucidate the gene expression and biological pathways altered in MCF7, breast cancer cells. The cytotoxicity to different cancer cell lines was screened using MTT assay and then whole gene expression was elucidated using microarray. The pathways selected also validated by quantitative PCR analysis, fluorometric and western blot assay. A total of 686 genes were found to have altered mRNA expression levels of two-fold or more in the 50 μM OXY-treated group, while 2,338 genes were differentially expressed in the 100 µM-treated group. The relevant visualized global expression patterns of genes and pathways were generated. Apoptosis was activated through mitochondria-lost membrane potential, caspase-3 expression and chromatin condensation without DNA damage. G0/G1 and S phases of the cell cycle control were inhibited dose-dependently by the compound. Rad51 gene (DNA repair pathway) was significantly down-regulated (P<0.0001). These results indicated that OXY moderated the key genes and pathways in MCF7 cells that could be developed as chemotherapy or chemosensitizing agent.